Виды рода Lepidocyrtus Bourlet, 1839 (Collembola, Entomobryidae, s. l.) в фауне СССР - Мартынова, Е.Ф.; Челноков, В.Г.; Расулова, 3.К. (Вестник зоологии, 1974)
An identification key is presented for nine species of genus Lepidocyrtus; 3 species are mentioned for the first time for the USSR.